Sleep´s quality and style of learning in students of human medicine at the National University Pedro Ruiz Gallo - Del Pielago Meoño, Aldo Fabrizzi (2013)
Introduction: In previous studies the frequency of sleep quality in medical students is high and the most common learning styles are the theoretical and reflective (assimilator modeled after Kolb). Previous studies made in Lima found frequencies of 64.5% and 58% of poor sleep quality. Also in another study found that in Spain and Chile dominated the predominant learning styles are reflective and theoretical is why we set as our objective: To determine the association between sleep quality and learning styles of medical students UNPRG. Material and Method: This cross-sectional study. The study population consisted of students of medicine UNPRG, working with a sample of 174. We measured the quality of sleep by Sleep Quality Index in Pittsburgh and learning styles with the Learning Style Questionnaire of Honey-Alonso, turning then to the Kolb model. Statistical analysis: Means, frequencies, chi-square and T-student, in addition estimate the prevalence ratio. Results: The frequency of poor sleep quality was 79.9%. The predominant learning style was assimilating at a frequency of 54.5% (95) (p> 0.05). Discussion: No association between sleep quality and learning styles. There was association between sleep quality and do sports or extracurricular academic activities, who had 32% less likely to have poor sleep quality.